Welfare reducing licensing by an outside innovator - Arijit Mukherjee; Uday Bhanu Sinha (Economic Theory Bulletin, 2024)
Abstract It is commonly believed that licensing of cost reducing technology increases welfare. We show that technology licensing by an outside innovator may reduce welfare when the technology is not useful for all final goods producers. Technology licensing reduces welfare if cost reduction by the licensed technology is small and the initial cost difference of the final goods producers is large. A higher intensity of competition, either due to lower product differentiation or due to Bertrand competition instead of Cournot competition, increases the possibility of welfare reducing licensing.
Additional information: D44;D45;L13
Keywords: 330; Auction; Fixed-fee; Outside innovator; Technology licensing; Welfare